Effect of Fiber Volume on The Flexural Strenght of Steel Fiber Reinfored Polyester Resin Composite - Al-Shabander, Ban; Mohammed, Awattif; Jaffer, Harith (Iraqi Journal of Science, 2023)
The aim of this study is to determine the flexural properties of steel fiber as a metal fiber and polyester resin as a matrix. The steel fibers were added to polyester resin at the various fiber volume fractions of 5, 10, and 15% steel fiber, and with different fiber orientations such as woven steel fiber type (0-45) ° and woven steel fiber type (0-90) ° indicate. Hand layup processes in these experiments were used to produce specimens test with the curing time of 24 hr. for the composite at room temperature. The results show that the flexural strength and flexural modulus values for 15 % vol.of woven steel fiber composite type (0-90) ° are (210MPa) and (2.29GPa( respectively. The results above indicate that the woven steel fiber (0-90) ° has a better bonding between its fiber and matrix compare to woven steel fiber type (0-45) °.